OPTIMASI JARINGAN DENGAN VIRTUAL LAN (VLAN) UNTUK MENINGKATKAN EFISIENSI DATA TRANSFER - Amisyah, Husnul; Fitriah (Department of Information System Muhammadiyah University of Riau, 2025)
Optimal network management is crucial in the digital era, where efficient data exchange is essential, especially in environments with numerous devices such as educational institutions and offices. The aim of this study is to evaluate the impact of implementing Virtual Local Area Networks VLAN on data transmission efficiency in computer networks. This research adopts an experimental quantitative approach through the simulation of two scenarios: networks without Virtual Local Area Networks VLAN and networks with VLAN, utilizing analytical tools such as Ping, iPerf, and Wireshark. The results show that implementing Virtual Local Area Networks VLAN can reduce average latency from 6.5 ms to 3.2 ms and increase throughput from 35 Mbps to 48 Mbps. Additionally, Virtual Local Area Networks VLAN significantly reduce broadcast traffic and packet collisions while enhancing data security through logical segmentation between departments. Therefore, Virtual Local Area Networks VLAN implementation greatly improves overall data communication efficiency and network performance.